PRINTED MASS MEDIA TO IMPROVE READING COMPREHENSION OF VOCATIONAL HIGH SCHOOL STUDENTS - Islamiyati, Dian Ayu (Widya Wacana: Jurnal Ilmiah, 2017)
ABSTRACTReading is one of the language skills needed to be taught in the classroom. Reading is also needed to be mastered by the students, in order to get some information from English text to increase their knowledge. The purpose of reading process is understanding what has been read. Therefore, it cannot be separated from comprehension. The aims of this research were to know whether the use of printed mass media can improve the reading comprehension and to describe the class condition when printed  mass  media  were implemented at  the  eleventh grade of SMK Plus Bhakti Oetama Gondangrejo in Academic Year of 2017/2018. This research was conducted at the Eleventh grade of SMK Plus Bhakti Oetama Gondangrejo. The method of the study was classroom action research which was conducted from August until October 2017. The data were collected through test and non-test. The tests consisted of pre-test and post-tests. While, non-tests consisted of observation, interview, field notes and documentation.  Furthermore,  the  researcher  used  qualitative  and  quantitative  data analysis to analyze the data. The results of the research showed that printed mass media improved the students’ reading comprehension. The mean score of pre-test was 51.46, post-test 1  was 69.96 and  post-test 2  was 79.96. T-test  was  used  to  compare the significance of teaching reading comprehension with df = n-1 = 25. In t-table values, significance 5% was 2.060 and significance 1% was 2.787. The result of pre-test and post-test 1 was significance which 2.060 < 17.452 > 2.787. Then t-test between post-test 1  and post-test 2  the result  was higher which 2.060  < 16.025 > 2.787. It can be concluded that using of printed mass media especially C’ n S Magazine improved students’ reading comprehension. Moreover, the class condition was more conducive after  they  used  texts  from  C’  n  S  Magazine.  A  lot  of  students  were  excited  and motivated during teaching learning process. Keywords: Reading Comprehension; Printed Mass Media; Classroom Action Research  ABSTRAKMembaca adalah salah satu keterampilan bahasa yang perlu diajarkan di kelas. Membaca juga perlu dikuasai oleh siswa, untuk mendapatkan beberapa informasi dari teks bahasa Inggris untuk menambah pengetahuan mereka. Tujuan dari proses membaca adalah memahami apa yang telah dibaca. Karena itu, tidak dapat dipisahkan dari pemahaman. Tujuan dari penelitian ini adalah untuk mengetahui apakah penggunaan media massa cetak dapat meningkatkan pemahaman membaca dan untuk menggambarkan kondisi kelas ketika media massa cetak dilaksanakan di kelas sebelas SMK Plus Bhakti Oetama Gondangrejo di Tahun Akademik 2017/2018. Penelitian ini dilakukan di kelas XI SMK Plus Bhakti Oetama Gondangrejo. Metode penelitian ini adalah penelitian tindakan kelas yang dilakukan dari Agustus hingga Oktober 2017. Data dikumpulkan melalui tes dan non-tes. Tes terdiri dari pre-test dan post-test. Sedangkan non-tes terdiri dari observasi, wawancara, catatan lapangan dan dokumentasi. Selanjutnya, peneliti menggunakan analisis data kualitatif dan kuantitatif untuk menganalisis data. Hasil penelitian menunjukkan bahwa media massa cetak meningkatkan pemahaman membaca siswa. Nilai rata-rata pre-test adalah 51,46, post-test 1 adalah 69,96 dan post-test 2 adalah 79,96. Uji-t digunakan untuk membandingkan pentingnya membaca pemahaman mengajar dengan df = n-1 = 25. Dalam nilai t-tabel, signifikansi 5% adalah 2.060 dan signifikansi 1% adalah 2.787. Hasil pre-test dan post-test 1 adalah signifikansi yaitu 2,060 <17,452> 2,787. Kemudian uji-t antara post-test 1 dan post-test 2 hasilnya lebih tinggi yaitu 2.060 <16.025> 2.787. Dapat disimpulkan bahwa menggunakan media cetak, terutama Majalah C 'n S meningkatkan pemahaman membaca siswa. Selain itu, kondisi kelas lebih kondusif setelah mereka menggunakan teks dari Majalah C 'n S. Banyak siswa yang bersemangat dan termotivasi selama proses belajar mengajar. Kata kunci: Pemahaman Membaca; Media Massa Cetak; Penelitian Tindakan Kelas